cytosolic trehalase from the thermophilic fungus Humicola grisea var. thermoidea - Cardello, L; Terenzi, H.F; Jorge, J.A (Microbiology (Society for General Microbiology), 1994)
A cytosolic trehalase was purified from the thermophilic fungus Humicola grisea var. thermoidea. The apparent molecular mass of the purified native enzyme was estimated to be 360 kDa by gel filtration chromatography. A single polypeptide band of approximate molecular mass 120 kDa was detected by SDS-PAGE, suggesting that the native enzyme was composed of three identical polypeptides. The carbohydrate content of the enzyme was estimated to be 12%. The pl of the enzyme, estimated by electrofocusing, was about 4.0. The purified trehalase was specific for trehalose and its activity was stimulated by manganese, calcium and cobalt and inhibited by aluminium chloride, copper sulfate, ADP and ATP. Sugars such as cellobiose, lactose, sucrose, fructose and maltose also showed some inhibitory effect which was abolished in the presence of calcium. The purified cytosolic trehalase exhibited an apparent Km of 0-86 mM, a pH optimum of 5.5 and an optimum temperature of 60 degrees C. Treatment with calcium induced disaggregation of the enzyme into three components. Apparently, calcium-induced disaggregation was not a prerequisite for calcium-mediated activation of the enzyme. The disaggregated trehalase was more labile to temperature than the native enzyme. The properties of the two H. grisea trehalases: the cytosolic enzyme and the conidial one, were compared.